Determination of the antimicrobial activity of oregano (Plectranthus amboinicus) extract against staphylococcus aureus and Escherichia coli - Fungo, Odina Lorraine B. (College of Home Economics, University of the Philippines Diliman, 2016)
The study aimed to assess the potential of the methanolic extract of local Plectranthus amboinicus as an antimicrobial against common pathogenic microorganisms in food. This was done by conducting disc diffusion assay, as well as determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract against Escherichia coli and Staphylococcus aureus. The observation of zones of inhibition greater than 7 millimeters in the disc diffusion assay showed that both microorganisms were susceptible to the extract, with E. coli showing more resistance due to its gram-negative nature. MIC determination specifically yielded an MIC of 10 milligrams per milliliter extract for S. aureus, and 15 milligrams per milliliter extract for E. coli. However, as growth was observed even at the highest concentration of 85 milligrams per milliliter extract for both microorganisms upon MBC determination, the methanolic P. amboinicus extract was concluded to be a bacteriostatic concentration-dependent antimicrobial. In order to further evaluate its activity and determine its specific mode of action, the identification of dominant antimicrobial compounds in the extract is recommended, as well as the comparison of activity of P. amboinicus extracted using different solvents. Furthermore, as the MIC varies depending on certain factors, it is also recommended that the MIC of the extract in actual food systems be determined.